2020
DOI: 10.1039/d0cc05627h
|View full text |Cite
|
Sign up to set email alerts
|

A delocalized cobaltoviologen with seven reversibly accessible redox states and highly tunable electrochromic behaviour

Abstract: CoII mediates electronic coupling between two N-Me-pyridinium-terpyridine ligands that are related to redox-active N,N'-dialkyl-4,4′-bipyridinium dications (viologens). Borderline Class II/III electronic delocalization imparts the cobaltoviologen complex with distinct electronic properties (e.g....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Cyclic voltammetry reveals that all complexes show at least one reversible oxidation for the M II /M III redox couple (in a 0.1 M NBu 4 PF 6 dichloromethane solution). [33] In case of 2 and 3 a second irreversible oxidation is observed (see Supporting Information).…”
Section: Cyclic Voltammetrymentioning
confidence: 98%
“…Cyclic voltammetry reveals that all complexes show at least one reversible oxidation for the M II /M III redox couple (in a 0.1 M NBu 4 PF 6 dichloromethane solution). [33] In case of 2 and 3 a second irreversible oxidation is observed (see Supporting Information).…”
Section: Cyclic Voltammetrymentioning
confidence: 98%
“…38–58 However, the color change in these systems is due to photoreduction of Mo/W 6+ ions through electron transfer inside the POM moiety under UV light, and the organic counter ion only acts as a stabilizer of the reduced POM. 59–62 In recent years, with the in-depth study of viologen-based photochromic compounds, 63–77 researchers have found that electron-deficient viologen ligands are capable of hybridizing with electron-rich POMs; this can not only form hybrid materials with diverse structures, but also bring more outstanding redox properties, photoactivity and thermal stability. 64,78–80 Currently, the viologen ligands used to construct POM-based photochromic hybrids have the following advantages: (1) viologen ligands, whose coordination sites are varied, can be easily modified, they can directly coordinate with the POMs or coordinate with transition metal ions first and then combine with POMs; (2) viologens not only act as counter ion but also take part in the coloration process, and can tune and optimize the photochromic property of POMs; (3) the combination of POMs with viologens can generate new properties in different fields such as photocatalysis, ultraviolet detection and so on.…”
Section: Introductionmentioning
confidence: 99%
“…5d). 24,36 The obvious positive shift indicates an effective improvement of oxidation ability which is anticipated to facilitate the oxygen evolution reactions. 37 The photophysical properties of these complexes were also investigated using UV-vis and low-temperature fluorescence spectroscopy.…”
Section: Resultsmentioning
confidence: 99%